2021
DOI: 10.4149/neo_2021_201122n1264
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of icotinib combined with concurrent chemoradiotherapy in locally advanced cervical cancer

Abstract: Concurrent chemoradiotherapy (CRT) based on cisplatin is recognized as the current standard treatment for locally advanced cervical cancer. The treatment of cervical cancer has reached a plateau in the last 20 years. Previous studies have proven that the epidermal growth factor receptor is correlated with chemo-and radioresistance and treatment failure. Hence, the purpose of this study was to investigate the efficacy and safety of icotinib combined with CRT in the treatment of locally advanced cervical cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Icotinib, an oral EGFR-TKI, modulates cell survival and proliferation by inhibiting the phosphorylation of tyrosine kinase in downstream signaling proteins, obstructing the activation of (15,(36)(37)(38)(39)(40). Both the EVIDENCE (38) and CONVINCE (41) studies demonstrated that icotinib considerably reduced DFS and serious adverse effects compared to chemotherapy for patients with EGFR-mutated lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Icotinib, an oral EGFR-TKI, modulates cell survival and proliferation by inhibiting the phosphorylation of tyrosine kinase in downstream signaling proteins, obstructing the activation of (15,(36)(37)(38)(39)(40). Both the EVIDENCE (38) and CONVINCE (41) studies demonstrated that icotinib considerably reduced DFS and serious adverse effects compared to chemotherapy for patients with EGFR-mutated lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (42) found that icotinib enhanced the radiation sensitivity of lung cancer cells by inhibiting the activation of MAPK/ERK/AKT pathway. Zhao et al (37) indicated that icotinib, combined with concurrent radiotherapy, was safe and effective in the treatment of locally advanced squamous cervical cancer. Wang et al (28) reported the favorable efficacy and safety of icotinib as a standalone treatment for EGFR-mutated esophageal cancer, suggesting that icotinib could be a viable treatment for elderly patients (43).…”
Section: Discussionmentioning
confidence: 99%
“…At present, operation, chemotherapy and radiotherapy are the most commonly used treatments for CC (5). The 5-year survival rate of patients with advanced CC is not high, only approximately 50% (6). In recent years, the incidence of CC has a rising and younger trend (7,8).…”
Section: Introductionmentioning
confidence: 99%